2007
DOI: 10.1016/j.biopsych.2006.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Volume in Offspring From Multiplex Alcohol Dependence Families

Abstract: Offspring from multiplex families for AD manifest genetic susceptibility by having larger cerebellar volume, which seems to be related to lesser grey matter pruning for age. Larger cerebellar volumes in adult obsessive compulsive disorder (OCD) patients have been reported. This suggests a possible similarity in structural underpinnings for alcohol dependence and OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
83
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 55 publications
8
83
3
1
Order By: Relevance
“…We do not have a clear-cut explanation for these associations. They may reflect the influence of factors other than alcohol on hippocampal size such as psychosocial stress (Smith, 1996;Winter and Irle, 2004), mood disorders (Campbell and Macqueen, 2004;Videbech and Ravnkilde, 2004), personality disorders (Laakso et al, 2000), withdrawal induced neurotoxicity (Crews et al, 2005;Prendergast et al, 2000), genetic susceptibility (Hill et al, 2006), or the modest size of our cohort. .…”
Section: Hippocampal Volumesmentioning
confidence: 98%
“…We do not have a clear-cut explanation for these associations. They may reflect the influence of factors other than alcohol on hippocampal size such as psychosocial stress (Smith, 1996;Winter and Irle, 2004), mood disorders (Campbell and Macqueen, 2004;Videbech and Ravnkilde, 2004), personality disorders (Laakso et al, 2000), withdrawal induced neurotoxicity (Crews et al, 2005;Prendergast et al, 2000), genetic susceptibility (Hill et al, 2006), or the modest size of our cohort. .…”
Section: Hippocampal Volumesmentioning
confidence: 98%
“…Some of the previously published studies examined differences in brain volume between groups in a dichotomous fashion, such as comparing youth with and without familial alcoholism (Hanson et al, 2010), whereas others took a similar approach but included ultra-high-risk youth with multiplex familial AUDs in the family history group, thereby comparing high-and low-risk groups with very distinct levels of vulnerability toward AUDs (Hill et al, 2001(Hill et al, , 2007(Hill et al, , 2009(Hill et al, , 2011(Hill et al, , 2013a(Hill et al, , 2013b. However, the current study examined the degree of familial risk for alcoholism and its relationship with brain volume in a large cohort of youth all considered at risk because of the presence of at least one second-degree relative with an AUD.…”
Section: Discussionmentioning
confidence: 99%
“…Research using a region of interest (ROI) approach has found greater cerebellar volume (Hill et al, 2007(Hill et al, , 2011 and consistently smaller amygdalar and hippocampal (Benegal et al, 2007;Hanson et al, 2010;Hill et al, 2001Hill et al, , 2013b volumes in youth and young adults with familial alcoholism compared with controls. This suggests that morphometric characteristics of the brain may be particularly important markers of risk, but that structural variation related to risk may be present across brain areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…alcohol use and cerebellar volume of healthy individuals have all been studied previously (Hutchinson et al;Keller et al, 2003;Laycock et al, 2008;Hill et al, 2007;Göçmen-Mas et al, 2009). In blind individuals, visual cortex and plasticity have also been studied profusely (Burton, 2003;Lambert et al, 2004).…”
mentioning
confidence: 99%